1986
DOI: 10.1111/j.1365-2125.1986.tb02830.x
|View full text |Cite
|
Sign up to set email alerts
|

Enalapril in moderate to severe hypertension: a comparison with atenolol.

Abstract: Patients with moderate to severe essential hypertension (mean untreated supine blood pressure 190/112 mm Hg) received once daily enalapril 20‐ 40 mg or atenolol 50‐100 mg, supplemented if required by hydrochlorothiazide 25‐100 mg, in a randomized observer‐blind trial. Both regimens produced a highly significant reduction in supine and standing blood pressure. There was no significant difference in the antihypertensive effects of enalapril and atenolol when they were used as monotherapy. After hydrochlorothiazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…[19] A study conducted for analysis of relationship between sodium status and ACE-inhibitor efficacy reported that sodium depletion boosts renin secretion from the juxtaglomerular cells which leads to increase in the hypotensive effect of ACE-inhibitor. [20] Postmenopausal women are especially salt sensitive. Tubular reabsorption of sodium is increased in these patients, which inhibits renin release, which decreases efferent arteriolar vasoconstriction leading to increased renal blood flow due to increased sodium excretion.…”
Section: Discussionmentioning
confidence: 99%
“…[19] A study conducted for analysis of relationship between sodium status and ACE-inhibitor efficacy reported that sodium depletion boosts renin secretion from the juxtaglomerular cells which leads to increase in the hypotensive effect of ACE-inhibitor. [20] Postmenopausal women are especially salt sensitive. Tubular reabsorption of sodium is increased in these patients, which inhibits renin release, which decreases efferent arteriolar vasoconstriction leading to increased renal blood flow due to increased sodium excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report a decrease in alertness with propranolol (e.g. Salem & McDevitt, 1984), another found mood-elevating and calming effects (Landauer et al, 1979) but most detected no major subjective effects (Webster et al, 1986). Atenolol in high dose (40 mg) exercised a transient calming effect (Salem & McDevitt, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Chrysant et al, 1983;Webster et al, 1986;Zezulka et al, 1987). Enalapril is administered orally, is itself inactive and undergoes hepatic deesterification to enalaprilat.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to mortality and morbidity, we really have no data on the effect of ACE inhibitors; we do know that they reduce blood pressure very adequately, producing the same reduction in diastolic -and an even greater reduction in systolic -blood pressure than ß-blockers [2,3]. It is tempting to as sume that a given reduction in blood pres sure produces the same mortality/morbidity benefit, irrespective of which drug is used.…”
Section: Essential Hypertensionmentioning
confidence: 99%